The development and renewal of money and transactions - László ARANY; Margit CSIPKÉS; Péter POPOVICS (Network Intelligence Studies, 2023)

(untitled)
In this article, we examine the history of the development of money and the importance and expansion of economic transactions, as well as two of the many currencies used in the European Union, the official currency of the EU, the euro, and the money of Hungary, the Hungarian forint. Money as an essential condition for material well-being. Money is the driving force of mankind. Money ensnares, keeps in motion, operates our world. Wherever we look, whatever we want to do, directly or indirectly, we will come into contact with money. The development of money, the market and banks is a series of events taking place in parallel.